2020
DOI: 10.21203/rs.3.rs-25134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eckol alleviates intestinal dysfunction during suckling-to-weaning transition via modulation of PDX1 and HBEGF

Abstract: Background Maintaining intestinal health in livestock is critical during weaning. Although intestinal dysfunction during this period can be alleviated by phlorotannins including eckol, the precise mechanisms are not fully understood. We addressed this question by evaluating changes in gene expression and intestinal function after treatment with eckol during the suckling-to-weaning transition. The biological roles of differentially expressed genes in intestinal development were investigated by assessing intest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Yuan et al [ 95 ] reported that by the dietary inclusion of flavones extracted from the leaves of Eucommia ulmoides enhanced intestinal morphology and integrity of diquat challenged pigs via improved intestinal barrier function. In addition, several other studies reported that supplementation of plant extract alone or in combination improved performance, digestibility, and intestinal barrier function in weaning pigs [ 77 , 78 , 79 ]. Ecklonia species (commonly known as brown algae) possessing a wide range of therapeutic properties, and enriched with vitamins, minerals, dietary fiber, proteins, and polysaccharide have received considerable attention in recent decades.…”
Section: Nutritional Intervention and Mechanistic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yuan et al [ 95 ] reported that by the dietary inclusion of flavones extracted from the leaves of Eucommia ulmoides enhanced intestinal morphology and integrity of diquat challenged pigs via improved intestinal barrier function. In addition, several other studies reported that supplementation of plant extract alone or in combination improved performance, digestibility, and intestinal barrier function in weaning pigs [ 77 , 78 , 79 ]. Ecklonia species (commonly known as brown algae) possessing a wide range of therapeutic properties, and enriched with vitamins, minerals, dietary fiber, proteins, and polysaccharide have received considerable attention in recent decades.…”
Section: Nutritional Intervention and Mechanistic Aspectsmentioning
confidence: 99%
“…In addition to this, a linear increase in overall average daily gain and feed efficiency ( Figure 1 ) in weaning pigs has been reported by Choi et al [ 96 ]. To evaluate the molecular mechanism of how eckol mitigate intestinal dysfunction, the changes in gene expression and intestinal function after Eckol treatment during the suckling-to-weaning transition were evaluated by Lee and Kim [ 79 ]. These authors investigated the biological roles of differentially expressed genes (DEGs) in intestinal development by assessing intestinal wound healing and barrier functions, as well as the associated signaling pathways and oxidative stress levels.…”
Section: Nutritional Intervention and Mechanistic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation